Long‐term remission in a case of plasmablastic lymphoma treated with COMP (cyclophosphamide, liposomal doxorubicin, vincristine, prednisone) and bortezomib. (19th January 2016) - Cencini, Emanuele; Fabbri, Alberto; Guerrini, Susanna; Mazzei, Maria Antonietta; Rossi, Vania; Bocchia, Monica
Abstract: Plasmablastic lymphoma (PBL) is a rare subtype of non‐Hodgkin lymphomas (NHL) strongly associated with HIV infection, even if cases in other immunosuppressed patients such as solid organ transplant recipients and in immunocompetent individuals have been increasingly reported. Current treatment strategy for HIV‐negative patients is similar to DLBCL as first‐line treatment, but durable remissions are seldom observed. Anthracycline‐containing regimens could be too toxic for elderly patients and/or with cardiac failure, because a non‐pegylated liposomal doxorubicin (NLD) could be used in this field. Bortezomib, a proteasome inhibitor currently approved for patients with multiple myeloma and relapsed mantle‐cell lymphoma, has recently showed clinical activity in PBL patients. Herein, we report a rapid and long‐term remission of a PBL patient with cardiac failure and that had previously received a double kidney transplant, treated front‐line with COMP (with a NLD substituted for doxorubicin) followed by subcutaneous bortezomib consolidation. We suggest first‐line treatment outcome is determinant for PBL patients. Bortezomib has a promising role and should be incorporated in future clinical trials and NLD could represent a suitable option for patients with cardiac failure or high cardiovascular risk.